The risk factors of type 2 diabetes in hypertensive subjects - Chen, Yingqun; Ma, Jiner; Lu, Donghui; Fang, Yefei (Frontiers in Endocrinology, 2022)
Objective: Hypertension and type 2 diabetes share common risk factors and usually co-occur. This study aimed to examine the relationship between hypertensive history and the incidence of type 2 diabetes in a Chinese hypertensive population. Methods: We recruited 443 essential hypertension (EH) subjects with T2DM (cases) and 443 EH subjects without T2DM (controls) matched to the cases by sex and age. The history of peak systolic blood pressure (SBP) was divided into 140-159 mmHg, 160-179 mmHg, and ≥ 180 mmHg, and the peak diastolic blood pressure (DBP) was divided into 90-99 mmHg, 100-109 mmHg, and ≥ 110 mmHg. Multiple binary logistic regression models were used to explore the association between hypertensive control status and T2DM. Results: Creatinine levels were higher in cases than in controls (P<0.05). The hypertension duration was longer in cases than in controls (14.7 years vs. 13.2 years; P<0.05). There were also significant differences in the history of the peak SBP and DBP in cases and controls (both P<0.05). Creatinine, hypertension duration, and family history of T2DM were risk factors for T2DM in essential hypertension (EH), with odds ratios (ORs) of 1.013 (1.004-1.022), 1.025 (1.003-1.047), and 5.119 (3.266-8.026), respectively. Compared with the lowest level of peak high DBP, the OR for T2DM at the highest level was 1.757 (1.074-2.969). In subgroups analyses, the effect of history of peak DBP to T2DM was significantly modified by gender (P-interaction=0.037). Conclusion: The highest DBP and hypertension duration were both independently associated with T2DM in hypertensive subjects